▼Agomelatine for major depressive episodes. Issue 8 (4th August 2010) - Unknown
Abstract : ▼Agomelatine (Valdoxan - Servier) is an antidepressant licensed for treating patients with major depressive episodes. The drug company's website for agomelatine states that the drug acts simultaneously as a melatonin receptor agonist and a serotonin receptor antagonist and claims that it is a "major therapeutic advance in management of depression through the restoration of circadian rhythms".1 Here we consider whether agomelatine offers significant advantage for patients with major depressive episodes.